Assessing Pre-Service Teachers' Competence in Teaching English to Young Learners - Jumrah, Jumrah; Sunra, La (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The purpose of this study is to assess pre-service teachers' competency in teaching English to young learners, with a focus on essential pedagogical and communicative skills. A mixed-methods approach was applied, utilizing quantitative surveys, standardized tests, semi-structured interviews, focus groups, and classroom observations. Data were gathered from 24 pre-service teachers in the English Education Department at the Faculty of Education and Teacher Training, UIN Mataram. Quantitative findings from Likert-scale questionnaires and standardized assessments indicate moderate confidence in pedagogical skills but reveal significant gaps in practical application, especially in lesson planning, classroom management, and adapting teaching strategies. The study highlights the need for comprehensive training in crafting age-appropriate lesson plans, employing diverse teaching styles, and establishing effective classroom management. Regarding communication, pre-service teachers were generally comfortable giving instructions and promoting participation but needed improvement in clarifying complex topics, providing constructive feedback, and adapting communication to varied student needs. Qualitative insights reveal that pre-service teachers often feel unprepared for real-world classroom challenges, underscoring the importance of hands-on training that mirrors classroom dynamics. Classroom observations confirm these findings by reflecting variation in instructional and communicative effectiveness. These results emphasize the need for teacher education programs to intensify practical, hands-on training, enhancing readiness for teaching English to young learners and contributing to a more robust foundation in pre-service teacher preparation.